Structure-mechanical model for plasto-elastic behavior of soft magnetic elastomers - Melenev, Petr Viktorovich; Kovrov, Vladimir Nikolaevich; Raikher, Yuriy Lvovich; Rusakov, Viktor Vladimirovich; Stepanov, Gennadiy Vladimirovich; Polygalova, Larisa Sergeevna; Kramarenko, Elena Yurievna (Computational Continuum Mechanics, 2014)
The effect of field-induced plasticity (magnetic shape memory) displayed by polymer composites filled with multi-domain ferromagnetic microparticles is discussed. Such a soft magnetic elastomer (SME) magnetizes, that is, the filler particles acquire magnetic moments only upon application of an external magnetic field. ‘Switching-on’ of interparticle magnetic interactions essentially affects the internal structure of SMEs since the magnetic forces by far exceed the high-elasticity ones due to attachment of the particles to the polymer matrix. According to the hypothesis, in a SME there self-organizes a network of clusters that gives birth to the effect of internal dry friction and by that imparts plasticity to the composite. Field-induced structuring, together with plasticity, disappears as soon as the external field is turned off. Under these conditions, elastic forces no longer experience any resistance and move the particles back to their initial spatial positions: the sample ‘recalls’ its initial shape. To account for the above-described plasto-elastic behavior of a magnetized SME, a structure-mechanical model (scheme) is proposed, which comprises the elastic elements (springs) and the entities (Saint-Venant elements) mimicking the dry-friction effect. The elements of the model are heuristically identified with two networks. One of them is related to the polymer matrix as itself, while another resembles the particle clusters formed due to the field-induced magnetic interactions. Both networks are interwoven and may deform only affinely. On the basis of the model, the tensile deformation cycles obtained in experiments on the two types of SMEs made of weakly-linked silicone rubber filled with carbonyl iron microparticles are interpreted. The tested SMEs differ by the dispersity of the filler. The samples of the first type contain only ‘fine’ iron particles with the size of 2-5 microns, while in the SME of the second type the filler consists of equal (by weight) amounts of ‘fine’ and ‘coarse’ (~70 microns) particles. The cycles measured under a number of external fields are presented. By fitting experimental data, the parameters of the theoretical scheme are evaluated, and their dependence on the applied field strength is determined. For the field dependencies of the scheme parameters of the isotropic SMEs examined here, the expressions borrowed from the phenomenology of textured SMEs are taken and tested, proving their applicability for this case.
Keywords: magnetoactive elastomers; magnetorheological polymers; magnetic field induced plasticity; elasto-plasticity; rheological behavior; magnetic shape memory